Self-Disclosure Through Instagram's Second Account: Alternative Media Interpersonal Communication of Introverted Students - Safina Afrilia Mulyanti; Khaerudin Imawan; Novicky Alban Adiputra (Journal of Comprehensive Science, 2026)
This study examines the phenomenon of self-disclosure among introverted students through the use of second Instagram accounts as an alternative medium for interpersonal communication. In the digital era, social media has become a dominant platform for identity expression; however, it also creates social pressure that influences how individuals manage their personal information. The objective of this research is to explore the forms of self-disclosure, the factors influencing its use, and the personal meanings attached to second Instagram accounts among introverted students. A qualitative phenomenological approach was employed, involving in-depth interviews with five purposively selected students and digital observation of their second Instagram account activities. The data were analyzed using thematic analysis based on DeVito's self-disclosure theory. The findings reveal that self-disclosure occurs in various emotional forms, including positive, negative, and neutral expressions, often conveyed through stories, captions, and visual content. The main factors driving the use of second accounts include the need for privacy, emotional safety, selective audience control, and psychological comfort. The second Instagram account is interpreted as a safe digital space that enables emotional release, self-reflection, and controlled identity management without social judgment. The study concludes that second Instagram accounts function as a strategic communication tool for introverted students to regulate self-disclosure and maintain emotional well-being. This research contributes to interpersonal communication studies by highlighting the role of digital privacy spaces in shaping authentic self-expression among introverted individuals.